Assessment of medical workers’ satisfaction with the organization of psychiatric care for patients at high risk of aggressive actions - A. V. Khodzhaev; I. N. Moroz; M. M. Skuhareuskaya (Military Medicine, 2026)
This ar ticle examines respondents’ satisfaction with the provision of psychiatric care in outpatient and inpatient settings for patients at high risk of aggressive behavior, with the results varying depending on the level of care provided. The main reasons for dissatisfaction with the organization of specialized medical care for patients with psychiatric problems were staffing (21.4 %), the lack of an effective system for preventing and monitoring aggressive actions of patients (21.5 %), insufficiently effective interaction between organizational structures of psychiatric care and law enforcement agencies (18.4 %) and social services (11.7 %), and the lack of interdepartmental programs for long-term support and reintegration of patients into society (14.7 %), the rating and values of which depended on the level of psychiatric care provided.